(untitled) (Ocean and Coastal Research, 2024)
The 2004 Sumatra-Andaman earthquake (9.3 Mw) and subsequent tsunami caused upliftment and subsidencethroughout the Andaman and Nicobar archipelago. This incident has significantly impacted the mangroves (97%vegetation loss) and coastal ecosystems of the Nicobar archipelago. Interestingly, the coastal subsidence hasalso created new intertidal habitats in the erstwhile agricultural lands and terrestrial forests, which provided anopportunity for the colonization of mangrove species. During our long-term monitoring of mangrove colonizationin the Nicobar archipelago, we collected Aegiceras corniculatum (L.) Blanco (Primulaceae) from Alreak,in Nicobar Islands. The occurrence of this species forms a new distributional record for the Nicobar archipelago.The present article provides detailed information on its taxonomy, ecology, and discusses the potential futurespread of this species in the Nicobar Islands.